MENTORING FOR JUNIOR HIGH SCHOOL SCIENCE TEACHERS IN PADANG CITY FOR CARRYING OUT DIY-SCIENCE EXPERIMENTS WITH LOCAL MATERIALS - Monica Prima Sari; Rahmah Evita Putri (Fakultas MIPA Universitas Negeri Padang, 2023)
The centralization of learning through a platform called Geschool to support Learning-From-Home in Padang city gives significant impacts to students’ learning competency, especially for science subject. Geschool provides the same materials and try-outs to all students and each lesson is scheduled at one time for all schools in the city. At this rate, there is a concern that science lesson could not be presented as its nature which is a process of gaining new knowledge which usually include laboratory work. This could lead to difficulty achieving the goal of science learning according to Kurikulum 2013. To address this concern, our team initiated a program to assist science teachers in SMP Negeri 15 and 34 Padang to conduct simple experiments with easily found local materials. Each participant was equipped with a pocket book containing 18 experiments relevant to the material for seventh, eight, and ninth grade. After the program ended, participants were required to submit a video of science experiment they did at home. Students’ responses to quiz and presentations of their own science experiments were taken as a measurement of scientific inquiry. Feedbacks from participants indicate eagerness to include these simple experiments as a part of science lesson onward.. Keywords — DIY-Science Experiments, Secondary School Science, Interest in Science Learning, Science Learning Activities, scientific inquiry